Evaluating the Impact of the Family-Friendly School Model on Enhancing Parental Engagement in Primary Education - ACHMAD , Sitti Fatimah; GANI , Hamsu Abdul; SUARDI (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2024)
This study investigates the effectiveness of the Family-Friendly School Model in promoting parental engagement in primary education. Recognized as a pivotal factor in student academic success and holistic development, parental involvement often encounters barriers such as communication breakdowns, mismatched expectations, and limited awareness of parental roles in education. The Family-Friendly School Model was designed as a structured approach to address these challenges, emphasizing open communication, mutual respect, and inclusivity. Using a mixed-methods research design that includes questionnaires, interviews, and observational data, the study reveals that implementing this model leads to notable improvements in parental engagement. Outcomes include higher attendance at school events, increased participation in parent-teacher meetings, and a strengthened partnership between schools and families. Additionally, the findings highlight the model's positive influence on student learning outcomes. The study underscores the need for continuous professional development for educators to maintain and enhance parental involvement. This research provides actionable insights into fostering sustainable collaboration between schools and families, affirming the Family-Friendly School Model as an effective strategy for strengthening primary education.